Costs and coverage. Pressures toward health care reform. - Lee, P R (1992)
Signs of discontent with the health care system are growing. Calls for health care reform are largely motivated by the continued increase in health care costs and the large number of people without adequate health insurance. For the past 20 years, health care spending has risen at rates higher than the gross national product. As many as 35 million people are without health insurance. As proposals for health care reform are developed, it is useful to understand the roots of the cost problem. Causes of spiraling health care costs include "market failure" in the health care market, expansion in technology, excessive administrative costs, unnecessary care and defensive medicine, increased patient complexity, excess capacity within the health care system, and low productivity. Attempts to control costs, by the federal government for the Medicare program and then by the private sector, have to date been mostly unsuccessful. New proposals for health care reform are proliferating, and important changes in the health care system are likely.